Conceptualising virtue in Sophocles’ Oedipus Tyrannus (2019)
This essay focuses on Oedipus Tyrannus, a Classical archetypal tragedy. Its spatial and temporal settings and characterisation situate this tragedy as an archetype for appraising the tragic hero. Given this canonical status among tragedies, scholars, since the Classical era, have attempted to appraise the underlying causes of Oedipus ' tragic fall from various perspectives. The question of free will and moral responsibility in the face of predestination as represented by Oedipus ' and his parents ' lives, is the crux in some of those studies. This paper, therefore, takes a trajectory different from this generic approach, shedding light on the admirable qualities of virtue which Oedipus possesses, as typified by the tough choices and decisions he gallantly makes in order to resolve the internal and external conflicts of identity and regicide-cum- parricide that plague him and the Thebans. The analysis carried out from the hermeneutics perspective evaluates Oedipus’ rather familiar ‘vices’ as having the inherent properties of Prudence, Justice, Fortitude, and Temperance, which make up the Aristotelian conceptualisation of virtue. It finds that justice in Sophocles' tragedy is a bifurcated fusion of divine will and retribution that often plays out on an innocent life as it happened in the case of Oedipus, who, along with his parents, consistently sacrifices any position of gain by birth and circumstance; and proactively bears the weight of his father’s misdeed even when that means paying the ultimate price in order to avert or revert the ill-fated curse placed on him before his conception. The study concludes that Oedipus’ actions are virtuous and worthy of emulation—not castigation—and that he should be regarded as a national hero and selfless leader, a model for the contemporary leaders and individuals. “I learnt that courage was not the absence of fear, but the triumph over it. The brave man is not one who does not feel afraid, but he who conquers that fear.” Nelson Mandela